INNOVATION ACTIVITIES OF FOOD INDUSTRY ENTERPRISES - Marzena Lemanowicz; Joanna Szwacka-Mokrzycka (Polityki Europejskie, Finanse i Marketing)
At present, the food market in Poland is characterised with significant intensity of competition, caused by high saturation of consumers’ needs. In response to market requirements, producers offer innovative product lines and diversified marketing activities. The article discusses the main trends related to initiating innovation activities in the segment of new generation products (dairy desserts and dessert concentrates). It has been concluded that innovation activities focus above all on changed product compositions, use of additives, form of consistence, offer diversification in terms of product weight, modification of packaging design and focus on distinguishing product positioning, as well as creation of unique segmentation and advertising strategies. Market leaders in terms of innovative product offers are large concerns and large processing plants. This is connected with high capital requirements of innovation activities. The dominant view is that innovation of the whole dairy industry in Poland is low. On the other hand, the situation in the segment of dessert concentrates is much better in this respect. Innovative activities ought to allow rationalisation of manufacturing costs, better quality and health characteristics of products.